2010
DOI: 10.1037/a0019880
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the link between racial discrimination and substance use: What mediates? What buffers?

Abstract: The relation between perceived racial discrimination and substance use was examined in two studies that were based on the prototype – willingness model (Gibbons, Gerrard & Lane, 2003). Study 1, using structural equation modeling, revealed prospective relations between discrimination and use five years later in a panel of African American adolescents (M age 10.5 at T1) and their parents. For both groups, the relation was mediated by anger/hostility. For the adolescents, it was also mediated by behavioral willin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
247
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(269 citation statements)
references
References 100 publications
(116 reference statements)
18
247
1
3
Order By: Relevance
“…Although this argues against reciprocal causation, longitudinal data are needed. Notably, longitudinal studies previously have shown that experiences of racial bias can affect subsequent levels of psychological stress (Brown et al, 2000) and that both racial bias and adverse emotional responses can affect the subsequent use of substances (Gibbons et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although this argues against reciprocal causation, longitudinal data are needed. Notably, longitudinal studies previously have shown that experiences of racial bias can affect subsequent levels of psychological stress (Brown et al, 2000) and that both racial bias and adverse emotional responses can affect the subsequent use of substances (Gibbons et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…People become more oriented toward health compromising behaviors, and efforts to refrain from temptations are more difficult. These responses may occur automatically (Richman, Boynton, Constanzo, & Banas, 2013) and may be mediated by affective responses such as anger (e.g., Gibbons et al, 2010).…”
Section: Behavioral Responsesmentioning
confidence: 99%
“…Em seguida, excluíram-se mais quatro artigos, após a leitura de seus conteúdos na ín-tegra, por não se tratarem de estudos originais ou não apresentarem medida de discriminação interpessoal autorrelatada como a principal exposição. Esse processo resultou em 34 estudos 15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35 . Adolescentes e adultos representaram a faixa etária estudada em 44% dos trabalhos (n = 12), apenas adolescentes 11% (n = 3) e crianças, adolescentes e adultos 11% (n = 3).…”
Section: Análises Estatísticasunclassified
“…Foi relatada moderação sobre o uso de substâncias por aculturação linguística e tempo de residência nos Estados Unidos 34 , presença de pais apoiadores 30 , e autoestima elevada 17 . Um estudo 42 relatou que raça/etnia moderou a relação entre a discriminação de gênero, estresse e uso de drogas durante a vida, exclusivamente para o subgrupo de mulheres latinas.…”
Section: Análises Estatísticasunclassified
See 1 more Smart Citation